Implementasi Pembelajaran Berbantuan Software Komputer dengan Pendekatan CTL untuk Meningkatkan Prestasi Belajar Mahasiswa pada Materi Uji Hipotesis Rerata Satu dan Dua Sampel - Ahmad Kholiqul Amin (LPPM Press, 2013)
Abstract:This research is a classroom action research (CAR) of 2 cycles qualitative approach. The purpose ofthis research is to improve the students’ achievement and interest in learning statistics. The target tobe achieved is 85% of the students that are complete in the classical study. The data collection usedis tests, questionnaires and the process of learning is by observation. In the first cycle, there is asignificant increase, although not reaching the target, from an average value of 68.8 to be 80 andthere is also an increase of interest from 40% to be 70%. After the improvement of the learningprocess, there is a significant increase in the second cycle, from an average value of 80 to be 95 andthere is also an increase of interest from 70% to be 85%. From the result above, it was concludedthat computer software-assisted learning using CTL approach can improve students’ achievementand learning interest of the fourth semester students of IKIP PGRI Bojonegoro in the academic year2012/2013.